Providers' perspectives on the performance of primary healthcare centres in India: The missing link. (6th May 2021) - Bangalore Sathyananda, Rajeshwari; Krumeich, Anja; Manjunath, Usha; de Rijk, Angelique; van Schayck, C. P.
Abstract: Background: Primary healthcare centres (PHCs) form the foundation of the Indian public health system, and thus their effective functioning is paramount in ensuring the population's health. The World Health Organisation (WHO) has set six aspects of performance assessment for general health systems, which are hardly applicable to the PHC setup in a low‐ and middle‐income country. The Primary Health Care Performance Initiative (PHCPI) has prescribed a framework with five domains consisting of 36 indicators for primary healthcare performance assessment from a policy point of view. For the assessment to be realistic, it should include inputs from stakeholders involved in care delivery, so this study examines the perspectives of healthcare providers at PHCs in India. Methodology: The authors used qualitative research methodology in the form of responsive evaluations of healthcare provider's interviews to understand the indicators of PHC performance. Results and Conclusion: The study results showed that healthcare providers considered efficient teamwork, opportunities for enhancing provider skills and knowledge, job satisfaction, effective PHC administration, and good community relationship as PHC performance assessment. These domains of performance could be considered the 'missing link' in PHC assessment, since they are deemed important by providers and did not coincide with the WHO aspects and the PHCPI performance assessment framework.